New Deterministic Protocol for Joint Remote Preparation of Two-qubit States - Don, Nung Van; An, Nguyen Ba; Bich, Cao Thi (Communications in Physics, 2012)
Designing quantum protocols with unit success probability is highly desirable from a viewpoint of the overall resource cost. In this work, we propose a new deterministic protocol for joint remote preparation of the most general two-qubit state using the same quantum/classical resource as in [An et al., Phys. Lett. A {\bf 375} (2011) 3570] and, at the same time, retaining the passive role of the receiver as in [Xiao et al., J. Phys. B: At. Mol. Opt. Phys. {\bf 44} (2011) 075501], which employs a different kind of nonlocal resource. From a practical point of view, this protocol proves most suitable in situations when only Einstein- Podelsky-Rosen pairs are supplied and the receiver is not capable of performing any measurements nor controlled-NOT gates.